(untitled) (Research, Society and Development, 2022)
The present study aimed to discuss shared custody making an analysis of its contribution to avoid parental alienation. When there is a dissolution of the marital relationship, they distance themselves, however, if there are children, it is necessary to pay attention to the legislation that establishes the obligation of upbringing and zeal for the offspring regardless of the marital rupture. In this sense, Law No. 11,698/2008 provides for shared custody, that is, parents jointly and harmoniously promote the upbringing, education and guidance of the child or adolescent. Living with parents is essential for the healthy development of children, being necessary for their emotional balance. It is understood that shared custody is a valuable instrument to break the cycle of parental alienation, a very serious violence that has consequences for the mental health of children. Furthermore, the practice of alienating the child can result in the loss of custody of the child, or even compensation. Therefore, the research is bibliographical with a descriptive character, presenting analysis of published studies and legislation. It was evidenced in the synthesis of the studies that the shared custody is an instrument that makes possible the maintenance of the familiar coexistence with the children attending to the constitutional principles in favor of the well-being of the children. The family is the unit considered the mother cell of society, so it is up to the State to regulate this coexistence in society.